2021
DOI: 10.1039/d1sm00337b
|View full text |Cite|
|
Sign up to set email alerts
|

Bilayer aggregate microstructure determines viscoelasticity of lung surfactant suspensions

Abstract: Premature infants are treated with replacement surfactants whose viscosity varies depending on the bilayer self-assembly in the dispersion, which determines how the material spreads from the trachea to the alveoli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(33 citation statements)
references
References 73 publications
3
26
4
Order By: Relevance
“…These results disclose a Newtonian behavior for the 40 g L -1 sample and a slightly viscoelastic behavior for the 80 g L -1 . In contrast to Ciutara and Zasadzinski [34], no yield stress behavior was found in the Curosurf® samples studied here. Of note here, the data from cone-and-plate rheology show good agreement with those of MRS technique (Fig.…”
Section: Iii2 -Viscosity Of Curosurf® Dispersion As a Function Of The...contrasting
confidence: 99%
See 2 more Smart Citations
“…These results disclose a Newtonian behavior for the 40 g L -1 sample and a slightly viscoelastic behavior for the 80 g L -1 . In contrast to Ciutara and Zasadzinski [34], no yield stress behavior was found in the Curosurf® samples studied here. Of note here, the data from cone-and-plate rheology show good agreement with those of MRS technique (Fig.…”
Section: Iii2 -Viscosity Of Curosurf® Dispersion As a Function Of The...contrasting
confidence: 99%
“…As a result, the concentration at which Curosurf® is formulated (80 g L -1 ) is associated with the volume fraction of 𝜙 = 0.42, suggesting that the vesicles are in a crowded environment. In support of this result, it should be noted that Lu et al had found volume fractions of vesicles in the order of 60% for Infasurf, another surfactant substitute [33] and more recently Ciutara and Zasadzinski reported values in the range 40-50% for Curosurf® and Survanta [34], in good agreement with our results. The 𝜙(𝑐)-relationship will be further useful to express the measured viscosity as a function of volume fraction and to compare it to rheological models of colloids.…”
Section: Iii1 -Structure Of Curosurf® Dispersionssupporting
confidence: 93%
See 1 more Smart Citation
“…Comparison of rheological data from Ciutara et al 21 and Thai et al 25 : Fig. 1 compares the results obtained by the two groups in dynamical frequency sweeps for 𝐺 ′ (𝜔) and 𝐺 ′′ (𝜔) and at 40 and 80 g L -1 .…”
Section: Introductionmentioning
confidence: 90%
“…[22][23][24] In 𝜂(𝜎)flow curves, where 𝜂(𝜎) is the shear viscosity at the applied shear stress 𝜎, the existence of a threshold stress is seen by a sharp decrease in viscosity at 𝜎 = 𝜎 𝑦 (Figure 2 from Ref. 21 ). The yield stress values obtained were on the order of 𝜎 𝑦 = 0.02 Pa for Infasurf® and Curosurf®, and 𝜎 𝑦 = 1 Pa for Survanta®.…”
Section: Introductionmentioning
confidence: 99%